2014
DOI: 10.1016/j.biomaterials.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal clodronate inhibition of osteoclastogenesis and osteoinduction by submicrostructured beta-tricalcium phosphate

Abstract: Bone graft substitutes such as calcium phosphates are subject to the innate inflammatory reaction, which may bear important consequences for bone regeneration. We speculate that the surface architecture of osteoinductive β-tricalcium phosphate (TCP) stimulates the differentiation of invading monocyte/macrophages into osteoclasts, and that these cells may be essential to ectopic bone formation. To test this, porous TCP cubes with either submicron-scale surface architecture known to induce ectopic bone formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 62 publications
13
98
0
Order By: Relevance
“…Taking these previous and current results together, it can be concluded that for both BCP and TCP -representing the most frequently investigated osteoinductive materials in the literature (Barradas et al, 2011) -surface microstructural dimensions of ~ 1 μm robustly promoted the formation of osteoclast-like cells concurrent with de novo bone formation. These results add to the growing consensus that osteoclast formation is prerequisite for osteoinduction (Davison et al, 2014a;Klar et al, 2013;Kondo et al, 2006;Le Nihouannen et al, 2005); however, it is still unknown what the exact role of osteoclasts is in this process. It has also been suggested that CaPs may stimulate bone formation by absorbing BMPs (bone morphogenetic proteins) endogenously synthesised near the implant surface (Klar et al, 2014;Ripamonti et al, 1993) or circulating in the blood .…”
Section: Nl Davison Et Alsupporting
confidence: 57%
See 2 more Smart Citations
“…Taking these previous and current results together, it can be concluded that for both BCP and TCP -representing the most frequently investigated osteoinductive materials in the literature (Barradas et al, 2011) -surface microstructural dimensions of ~ 1 μm robustly promoted the formation of osteoclast-like cells concurrent with de novo bone formation. These results add to the growing consensus that osteoclast formation is prerequisite for osteoinduction (Davison et al, 2014a;Klar et al, 2013;Kondo et al, 2006;Le Nihouannen et al, 2005); however, it is still unknown what the exact role of osteoclasts is in this process. It has also been suggested that CaPs may stimulate bone formation by absorbing BMPs (bone morphogenetic proteins) endogenously synthesised near the implant surface (Klar et al, 2014;Ripamonti et al, 1993) or circulating in the blood .…”
Section: Nl Davison Et Alsupporting
confidence: 57%
“…In support of this theory, it has been reported that osteoclastogenesis precedes osteoinduction by microstructured TCP by several weeks (Akiyama et al, 2011;Kondo et al, 2006), and osteoclast depletion limits (Ripamonti et al, 2010) or completely blocks de novo bone formation by osteoinductive CaPs (Davison et al, 2014a). Recently, we reported a clear link between TCP microstructure, osteoclastogenesis, and subsequent de novo bone formation (Davison et al, 2014a;Davison et al, 2014b). However, (pre-)osteoclast differentiation and activity is influenced by multiple substrate parameters including surface nano-/microroughness (Makihira et al, 2007;Webster et al, 2001), solubility (Benahmed et al, 1996;Yamada et al, 1997), and the accompanied release of nano-/microparticulate (Fellah et al, 2007;Velard et al, 2013), so it is currently unknown if this link also holds true for less resorbable materials like BCP or titanium.…”
Section: Nl Davison Et Al Osteoinduction and Osteoclastogenesis By Bmentioning
confidence: 89%
See 1 more Smart Citation
“…The rate of resorption needs to be optimized depending on the intended purpose and be balanced with bone tissue regeneration for successful clinical treatments. Moreover, recent findings suggest that the optimized resorption or degradation of calcium phosphates itself can enhance bone tissue regeneration through an immunomodulatory action [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of osteoinductive calcium phosphate ceramics in bone repair was reported to be equal to autografts when implanted in critical-sized defects, suggesting their potential as promising alternatives of autologous bone crafts [109]. Nonetheless, it is not fully understood so far how surface microstructure could bring such responses, but protein adsorption [110], osteogenic differentiation of osteoblast progenitors [108,[111][112][113][114][115] as well as early activation of osteoclastogenesis [116][117][118][119] on the surface have been suggested. Moreover, there are multiple routines to obtain synthetic bone substitutes with such desired property [120].…”
Section: Approaches To Improve the Bone Forming Ability Of Synthetic mentioning
confidence: 99%